Organic/Inorganic Hybrid Fibers: Controllable Architectures for Electrochemical Energy Applications - Fangzhou Zhang (Wiley, 2021)
Abstract Organic/inorganic hybrid fibers (OIHFs) are intriguing materials, possessing an intrinsic high specific surface area and flexibility coupled to unique anisotropic properties, diverse chemical compositions, and controllable hybrid architectures. During the last decade, advanced OIHFs with exceptional properties for electrochemical energy applications, including possessing interconnected networks, abundant active sites, and short ion diffusion length have emerged. Here, a comprehensive overview of the controllable architectures and electrochemical energy applications of OIHFs is presented. After a brief introduction, the controllable construction of OIHFs is described in detail through precise tailoring of the overall, interior, and interface structures. Additionally, several important electrochemical energy applications including rechargeable batteries (lithium‐ion batteries, sodium‐ion batteries, and lithium–sulfur batteries), supercapacitors (sandwich‐shaped supercapacitors and fiber‐shaped supercapacitors), and electrocatalysts (oxygen reduction reaction, oxygen evolution reaction, and hydrogen evolution reaction) are presented. The current state of the field and challenges are discussed, and a vision of the future directions to exploit OIHFs for electrochemical energy devices is provided.